FAMILY ROLE MODELING, PROJECT-BASED LEARNING, AND AUDIO-VISUAL MEDIA: ITS INFLUENCE ON ISLAMIC EDUCATION INTEREST AND ACHIEVEMENT - Ahmad Fahmi; Abd Haris; Shonhadji Shonhadji (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
The study aimed to analyze the influence of family role modeling education, the implementation of the Project-Based Learning method, and the use of audio-visual learning media on students’ learning interest and academic achievement. This research employed a quantitative approach using a survey design involving students from Islamic junior high schools in Gunung Sindur District, Bogor Regency. Data were collected through questionnaires developed based on indicators of the research variables and analyzed using Structural Equation Modeling based on Partial Least Squares to examine the relationships among variables in the proposed research model. The results indicate that family role modeling education, the Project-Based Learning method, and the use of audio-visual learning media have a positive and significant relationship with the improvement of students’ learning interest. Furthermore, students’ learning interest was found to contribute significantly to the improvement of their academic achievement in Islamic Religious Education. These findings demonstrate that the combination of family support, the implementation of project-based instructional strategies, and the use of engaging learning media can create a more interactive and effective learning experience for students. This study indicates to the development of educational practices by emphasizing the importance of synergy between the family environment, pedagogical innovation, and the use of educational technology in improving the quality of the learning process and students’ learning outcomes.